DEFINICIÓN DE UNA NUEVA FASE CONSTRUCTIVA EN HUACA PUCLLANA - Ganoza Yaipén, Mirella (2017)
In the Ceremonial Center Huaca Pucllana, at the sixth platform, it found elements by their formal features and technology used correspond to a phase of occupation; in the case of Huaca Pucllana would be the Construction Phase IV, which would complement the design information and architectural growth of the Great Pyramid and its superposition on the previous phases.